Pneumoperitoneum due to perforated appendicitis: a rare anatomo-radiologic correlation - Rodrigues,André Luiz Santos (2008)
BACKGROUND: Pneumoperitoneum is usually associated with a perforated peptic ulcer. However, perforated appendicits may be evolved on it. In the medical literature, the anatomo-radiologic correlation between them is an uncommon event. CASE REPORT: Man with 56-year-old look for assistance with diffuse abdominal pain and distension associated with fever, vomit and absence of flatus and evacuation for about 14 days. The chest radiography revealed a pneumoperitoneum. Diffuse peritonitis was found during the exploratory laparotomy. Appendectomy, peritoneal cavity cleaning and drainage with tubular drains were carried out. However, severe sepsis occurred and the patient died on the 16th post-operative day with multiple systemic organ failure. CONCLUSION: Although rare as pneumoperitoneum ethiology, acute appendicitis may be thought as it's cause.